(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
Short-run production control charts have been evolved from simple nominal and target value charts to t-charts and EWMA t-charts as suggested on a constant sampling interval. The standard Shewart chart is not appropriate to be implemented on company “X”, that produces powder coating paint, which production process runs on small batches at a limited production time. This paper discusses the application of t-charts and EWMA t-charts in comparison with I-MR and Z-MR charts on company X’s production line. We have found that t-charts and EWMA t-charts are more sensitive to detect the out of control condition.